Digital economy development and global value chain network centralization - Hankun Yuan; Mingyang Yue; Rong Wang; Biao Ren; Xueyang Li (PLoS ONE, 2025)
The development of the digital economy significantly relies on promoting economic liberalization and achieving high-end embedding of manufacturing into the global value chain (GVC). Based on the heterogeneous firm model, this paper introduces the factors of digital economy development, aggregates the production behavior of firms at the national level, and empirically examines the effects of digital economy development on the centralization of the GVC network and the internal mechanisms. The results show that the development of the digital economy significantly enhances a country’s centralization of GVC network, primarily through enhancing productivity and alleviating resource misallocation. Meanwhile, digital economy development contributes more to the centralization of the GVC network in developed countries and high institutional quality industries. Further analysis shows that digital economy development not only enhances a country’s centralization of GVC network but also extends the length of a country’s GVC and promotes a country to climb up the GVC.